Antifungal and biofilm inhibitory effect of Cymbopogon citratus (lemongrass) essential oil on biofilm forming by Candida tropicalis isolates; an in vitro study. (10th January 2020) - Sahal, Gulcan; Woerdenbag, Herman J.; Hinrichs, Wouter L.J.; Visser, Anita; Tepper, Pieter G.; Quax, Wim J.; van der Mei, Henny C.; Bilkay, Isil Seyis
Abstract: Ethnopharmacological relevance: Cymbopogon citratus (lemongrass) essential oil has been widely used as a traditional medicine and is well known for antimicrobial properties. Therefore, it might be a potent anti-infective and biofilm inhibitive against Candida tropicalis infections. Until now, no ideal coating or cleaning method based on an essential oil has been described to prevent biofilm formation of Candida strains on silicone rubber maxillofacial prostheses, voice prostheses and medical devices susceptible to C. tropicalis infections. Aim of the study: To investigate the antifungal and biofilm inhibitory effects of Cymbopogon citratus oil. Clinical isolates of C. tropicalis biofilms on different biomaterials were used to study the inhibitory effect. Materials and methods: The efficacy of Cymbopogon citratus, Cuminum cyminum, Citrus limon and Cinnamomum verum essential oils were compared on biofilm formation of three C. tropicalis isolates on 24 well polystyrene plates. C. citratus oil coated silicone rubber surfaces were prepared using hypromellose ointment as a vehicle. The antifungal tests to determine minimum inhibitory and minimum fungicidal concentrations were assessed by a microbroth dilution method and biofilm formation was determined by a crystal violet binding assay. Results: C. tropicalis strains formed more biofilm on hydrophobic materials than on hydrophilic glass. C. citratus oil showed a high antifungal effect against all C. tropicalis strains. For comparison, C. limon oil and C. cyminum oil showed minor to no killing effect against the C. tropicalis strains. C. citratus oil had the lowest minimal inhibitory concentration of all essential oils tested and inhibited biofilm formation of all C. tropicalis strains. C. citratus oil coating on silicone rubber resulted in a 45–76% reduction in biofilm formation of all C. tropicalis strains. Conclusion: Cymbopogon citratus oil has good potential to be used as an antifungal and antibiofilm agent on silicone rubber prostheses and medical devices on which C. tropicalis biofilms pose a serious risk for skin infections and may cause a shorter lifespan of the prosthesis. Graphical abstract: Image 1